History of Leukemia: Diagnosis and Treatment from Beginning to Now: - Mehranfar, Sahar; Zeinali, Sirous; Hosseini, Rana; Akbarzadeh, Abolfazl; Mohammadian, Mozhdeh; Pour Feizi, Abbasali Hossein (Galen Medical Journal, 2017)
In 1845, leukemia was known as a systemic illness; and it was more than 100 years later that the first report of a significant therapy for leukemia was published in 1948. Leukemia was known as a multifactorial disease rather than a single disease till 1900. In 1965, less than 1% of children with acute leukemia were predictable to have long-term survivors; today, approximately 80% of children and adolescents with acute lymphoblastic leukemia are cured, these achievements are due to the cooperative effort of researchers and physicians in the field. Despite this success, leukemia is still the leading cause of death globally. This review aims to elucidate the history of leukemia from the beginning of the 19th century when scientists defined unusual disorders of the blood cells, till present. Additionally, we tried to discuss the history of the diagnosis and treatment of leukemia with particular emphasis on acute leukemia. [GMJ.2017;6(1):12-22]